Study of all-optical switching properties of zinc phthalocyanine thin film by pump-probe technique. (1st October 2017) - Kumar, Anil; Punia, Rajesh; Gupta, Arun K.; Mohan, Devendra; Kapoor, Kirti
Highlights: Nonlinear optical coefficients of Zn(II)Pc are measured by z-scan technique. Probe beam modulation by pump beam is investigated indicating nonlinearity of dye. All-optical switching in Zn(II)Pc is realized by pump-probe experiment. Excited state absorption is the responsible mechanism for all-optical switching. Abstract: The nonlinear optical absorption, refraction and switching behavior of Zinc phthalocyanine (Zn(II)Pc) thin films are reported. Z-scan technique is employed to study the nonlinear absorption and nonlinear refraction behavior of the thin films with nanosecond pulses of Nd:YAG laser at ∼532 nm. Optical switching behavior of the dye is studied using pump-probe technique with ∼5 ns pulses of Nd:YAG at ∼532 nm as the pump beam and ∼632.8 nm cw He-Ne laser as the probe beam. The switching behavior of the dye is attributed to excited state absorption (ESA) of the probe beam by the dye molecules. Probe beam modulation with increasing pump intensity is also investigated.